Pengaruh NCT Dream Sebagai Brand Ambassador Dan Brand Image Terhadap Keputusan Pembelian Produk Lemonilo - Ugis Picha Azzahra (Soratekno Publisher, 2025)
This study aims to determine the influence of NCT Dream as a Brand Ambassador and Brand Image on the Purchase Decision of Lemonilo products at STIE Insan Pembangunan. The research method used is a quantitative approach. The population in this study consists of management students at STIE Insan Pembangunan. The sampling technique employed is non-probability sampling using purposive sampling, with a total of 94 respondents who are Lemonilo product consumers at STIE Insan Pembangunan. Primary data was collected through questionnaires distributed to respondents and processed using the SPSS program. The research findings indicate that NCT Dream as a Brand Ambassador has a significant influence on the Purchase Decision of Lemonilo products, with a t-value greater than the t-table value (4.561 > 1.66177). Brand Image also has a significant impact on the Purchase Decision of Lemonilo products, with a t-value greater than the t-table value (4.021 > 1.66177). Additionally, NCT Dream as a Brand Ambassador and Brand Image simultaneously have a significant influence on the Purchase Decision of Lemonilo products, with an F-value greater than the F-table value (12.979 > 2.36).